The prophet - Gibran, Kahlil; Kaur, Rupi
"In Kahlil Gibran's inspirational masterpiece--the most famous work of spiritual fiction of the twentieth century--a prophet named Almustafa is about to board a ship to travel back to his homeland after twelve years in exile when he's stopped by a group of people who ask him to share his wisdom before he leaves. In twenty-eight poetic essays, he does so, offering profound and timeless insights on many aspects of life, including love, pain, friendship, family, beauty, religion, joy, sorrow, and death. An immediate success when it was first published in 1923, The Prophet is a modern classic, having been translated into more than forty languages and sold more than nine million copies in the United States alone. The message it imparts, of finding divinity through love, made it the bible of 1960s culture and continues to touch hearts and minds across generations and national borders. This edition is illustrated with twelve of Gibran's famous visionary paintings and features a foreword by Rupi Kaur"--
First published in the United States of America by Knopf, 1923.
Keywords: Prose poems, American; Mysticism; BODY, MIND & SPIRIT / Inspiration & Personal Growth; FICTION / Visionary & Metaphysical; PHILOSOPHY / Religious